Projecting lower competence to boost apology effectiveness: Underlying mechanism and boundary conditions - Antonetti, Paolo; Baghi, Ilaria (Journal of the Academy of Marketing Science, 2023)
Apologies represent a common strategy to respond to crises or product/service failures. In five experiments, involving different failures, we show that projecting lower competence in a specific, non-core domain of activity provides a significant boost to apology effectiveness. A projection of lower competence, operationalized as a lack of skills or expertise required to effectively execute a specific task, increases the perceived costliness of the apology because the organization accepts a symbolic cost. Perceived costliness, in turn, increases the perceived sincerity of the apology and leads to more favorable responses. This strategy, however, is effective only under certain circumstances and can backfire if misapplied. First, organizations might project lower competence only when stakeholders have no other reason to question their competence. Second, projecting lower competence is effective only when the failure is not relevant to the core business. Finally, the strategy is not effective for consumers with low communal relationship orientation.